APLIKASI TEKNIK PENGINDERAAN JAUH UNTUK IDENTIFIKASI MULUT GUA DAN SEBARANNYA DI KAWASAN KARST DAERAH SEMANU, GUNUNGKIDUL, YOGYAKARTA - , EFENDI SAPUTRA; , Drs. Retnadi Heru Jatmiko, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Karst region known as barren land due to the potential stored in it in the form of an underground river ,as well as beauty Speleotem isnât widely known by the people . The development of resources satellite technology at this time, already widely used for various disciplines of science, especially for the geological mapping purposes and related studies. The study aims to analysis of Landsat 8 Pancrhomatic remote sensing imagery to identification and to discover the distribution of the cave entrance in the study area. Remote sensing techniques application for the identification of the cave entrance in this study using an the approach flow pattern analysis, structural analysis, and morphological analysis. The variables used are flow patterns, straightness and negative morphology and vegetation obtained through visual interpretation process This result is remote sensing techniques to identify the cave entrance in the karst region with the approach flow pattern analysis, structural analysis, and morphological analysis have accuracy level 72%. That remote sensing techniques can be used to identify entrance of the cave.